The Usia dan Jenis Kelamin Berpengaruh terhadap Kejadian Covid-19 di Rumah Sakit Al-Islam Bandung - Anisa Putri Dinanti (Bandung Conference Series: Medical Science, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) originating from China. This is to determine the age and sex that is easily affected by the COVID-19 virus. This study is an observational analytical study with a cross-sectional design. Samples are taken using secondary data i.e. from the patient's medical record. Sampling in this study was taken using a total sampling technique using 1,758 medical record data of patients confirmed positive for COVID-19 who were treated at Al-Islam Hospital Bandung for the 2021 period. Data analysis using chi square test. The results showed that most of the COVID-19 patients at Al-Islam Hospital in Bandung City for the 2021 period were aged 46−65 years, namely 918 people (52.2%) and a small part in the age group of 18−25 years as many as 48 people (2.7%). These results are in accordance with research conducted by the Center for Strategic and International Studies (CSIS) Commentaries 2020 that the largest proportion of COVID-19 patients in Indonesia is in the age range of 50−59 years, which is 20.9 percent of the total positive cases of COVID-19. Hasil research on characteristics based on sex in COVID-19 patients at Al-Islam Hospital Bandung City for the 2021 period was male, namely 903 people (51.4%) and a small percentage of female sex as many as 855 people (48.6%). These results are in accordance with research conducted by Fanny Maler with the results of research found that more men contract COVID-19 while women are fewer. There is a relationship between age and gender with the incidence of COVID-19 at Al-Islam Hospital Bandung.